The Concept of Prophet Ya‘qub a.s. Parenting and its Relevance to the Birrun Wālidain of Prophet Yusuf a.s: A Study of Tafsīr Asy-Sya‘rāwī - Indah Rahmadita; Mahmudin Bunyamin; Mustamira Sofa Salsabila (Jurnal test, 2026)
The decline of filial ethics in contemporary society indicates the weakening of value-based parenting within the family. Although Surah Yusuf presents an exemplary model of parent-child relationships, previous studies have not specifically examined the relationship between parenting patterns and the formation of filial piety (birrun wālidain) within the perspective of Tafsīr Asy-Sya‘rāwī. This study examines the parenting concept of Prophet Ya‘qub (a.s.) and its relevance to the formation of birrun wālidain in Prophet Yusuf (a.s.). It employs a qualitative library approach using the thematic (maudhu‘i) method by analyzing selected verses of Surah Yusuf. The primary source is Tafsīr Asy-Sya‘rāwī, supported by relevant scholarly literature. The findings reveal two integrated parenting patterns: (1) affectionate communication combined with preventive protection, and (2) strategic guidance accompanied by the cultivation of tawakkul. These patterns function as a continuous process of value internalization that shapes filial piety as an internalized character rather than a spontaneous attitude. This study concludes that Qur’anic parenting in Surah Yusuf offers an integrative model of family education that connects emotional, moral, and spiritual dimensions, and is relevant for addressing the contemporary decline of filial ethics.